People Seeking Asylum in Australia and their Access to Employment: Just What Do We Know? - Caroline Fleay; Anita Lumbus; Lisa Hartley (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2016)
Public and political claims about the employment of people from a refugee background in Australia do not always reflect the research findings in this area. For example, recent claims by a senior Coalition Government Minister about people seeking asylum who arrived to Australia by boat during the previous Labor Government’s terms in office (2007-13) posit that many have limited employment prospects. However, given there is little research or government reporting on the experiences of asylum seekers who arrived during this time, and none that focuses specifically on their employment, there is no evidence to support this. A review of research on the employment experiences of people from a refugee background, and Australian policies, suggests a more nuanced picture. This includes research that found while initially people from a refugee background are more likely to be unemployed, have temporary jobs and lower incomes than other newly arrived immigrants, over the longer term second-generation refugees have higher levels of labour market participation than the general population and refugees and their families make significant economic and community contributions to Australia. Research also highlights that refugees may experience a range of barriers to accessing employment, including discrimination, and a review of Australian policies indicates these are likely to have exacerbated some of these barriers for asylum seekers who arrived to Australia by boat. In addition, given previous findings that public attitudes can be influenced by representations made in public and political discourses, the public statements of senior Ministers may be further deepening barriers to accessing employment faced by asylum seekers who arrived by boat.